Legal aspects of product safety: a case of infant food - Loganathan Krishnan, (Fakulti Undang - Undang, 2007)

(untitled)
The Food Safety Unit, Division of Food and Nutrition, World Health Organization reported, that every year, there are 1500 million diarrhoea cases in children under the age of five and 10.5 million die as a result. Such state of affairs raises pertinent issues concerning infant food. Thus, this study investigates the legal aspects of safety of infant food. The study examines the statutory provisions of the Food Act 1993 and Food Regulation 1985 since they govern and regulate infant food. Secondary data are collected from various bodies. The study analyses the data to determine the safety aspects of infant food. The data unfolds the extent manufactures comply with the safety standards as prescribed by the laws. The study then explores the role of the relevant authorities in ensuring food safety ant national level. The study also explores whether the relevant authorities act as effective watchdogs to monitor and enforce the prescribed safety standards and the extent this are carried out. The study then analyses whether the prescribed safety standards at national level are in tandem with international safety standards. Finally, the study unveils whether the problem lies with the safety standards of infant food, the governing and regulating laws or the enforcement of the laws